2013
DOI: 10.1038/ncb2721
|View full text |Cite|
|
Sign up to set email alerts
|

A global analysis of SNX27–retromer assembly and cargo specificity reveals a function in glucose and metal ion transport

Abstract: The PDZ domain-containing sorting nexin 27 (SNX27) promotes recycling of internalized transmembrane proteins from endosomes to the plasma membrane by linking PDZ-dependent cargo recognition to retromer-mediated transport. Here, we employed quantitative proteomics of the SNX27 interactome alongside quantification of the surface proteome of SNX27 and retromersuppressed cells to dissect the assembly of the SNX27 complex and provide an unbiased global view of SNX27-mediated sorting. Over 100 cell surface proteins,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

52
795
2
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 474 publications
(854 citation statements)
references
References 32 publications
52
795
2
5
Order By: Relevance
“…In contrast, no type II receptors were found to be down-regulated. A more distant homolog of SMA-6, TGFβR1 (ALK5) (transforming growth factor-β receptor type I/activin-like kinase 5), was also suggested to be down-regulated in VPS35-and SNX27-depleted HeLa cells (33). Although a recent study failed to show a VPS35 RNAi effect in Madin-Darby canine kidney cells on TGFβR1(ALK5) (34), they did demonstrate that TGFβRII was mislocalized to both the basolateral and apical membrane, as opposed to its normal localization to the basolateral membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, no type II receptors were found to be down-regulated. A more distant homolog of SMA-6, TGFβR1 (ALK5) (transforming growth factor-β receptor type I/activin-like kinase 5), was also suggested to be down-regulated in VPS35-and SNX27-depleted HeLa cells (33). Although a recent study failed to show a VPS35 RNAi effect in Madin-Darby canine kidney cells on TGFβR1(ALK5) (34), they did demonstrate that TGFβRII was mislocalized to both the basolateral and apical membrane, as opposed to its normal localization to the basolateral membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our findings regarding the interplay of BMP receptor trafficking and signaling outputs have important implications for related receptors throughout metazoan phylogenies. Recently, two close vertebrate homologs of SMA-6, BMPRIA(ALK3) (bone morphogenetic protein type IA receptor/activin-like kinase 3) and ACVRIB(ALK4) (activin receptor type IB/activin-like kinase 4), were identified to be downregulated in a proteomic study for cell-surface receptors altered by SNX27-and VPS35-depleted human HeLa cells (33).…”
Section: Discussionmentioning
confidence: 99%
“…Detailed proteomic analysis conducted in mammalian cell lines has revealed that a loss of SNX27 expression results in the downregulation of multiple membrane proteins (81). Recent evidence has linked mutations in the SNX27 gene to Down's syndrome and infantile myoclonic epilepsy (82) (83).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…To date SNX27 appears to contribute to cargo recycling primarily through PDZ-dependent mechanisms. 5 In addition to cargo recognition, the SNX27 PDZ domain mediates interaction with the vacuolar sorting 26A (VPS26A) retromer subunit. 5,11 As a result, SNX27 mediates endosomal recycling together with the retromer protein assembly, and the actin remodeling Wiskott-Aldrich syndrome and SCAR-homolog (WASH)-containing multiprotein complex called the WASH Regulatory Complex (SHRC).…”
Section: Introductionmentioning
confidence: 99%
“…4 In addition, SNX27 binds ubiquitously expressed transmembrane cargos such as glucose and metal ion transporters that have a class I PDZ binding motif (PDZ-bm). 5 With SNX17 and SNX31, SNX27 is classified as a SNX-FERM protein. These proteins have an atypical FERM domain (4.1, ezrin, radixin, moesin) responsible for binding cargos bearing a Phe-XaaAsn-Pro-Xaa-Tyr (FxNPxY) sequence for recycling.…”
Section: Introductionmentioning
confidence: 99%